2022
DOI: 10.1155/2022/6193082
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Oil Recovery Performance of CO2 Huff-and-Puff Process in Fractured Tight Oil Reservoirs

Abstract: In order to investigate energy supply capacity and oil production contribution of near-fracture and fracture-free zone in fractured tight oil reservoirs, a series of CO2 huff-and-puff tests were designed and carried out in different experimental conditions. A fracture-matrix long-core system was established to simulate the near-fracture zone and matrix zone of tight oil reservoirs. The NMR technique was utilized to identify the microscopic remaining oil of certain core samples. The effects of fracture length, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…41 Qian et al studied the liquid production capacity of fractured and nonfractured ends of fractured tight oil reservoirs by changing the fracture length, soaking time, and depressurization method. 42 The results show that increasing the fracture length can improve the recovery rate and the recovery rate of the pore in the core near the fracture end is effectively improved. Bejestani et al studied the effects of porosity and permeability of the rock matrix on oil recovery when CO 2 is injected under different miscible conditions (primary miscible, near miscible, and immiscible).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…41 Qian et al studied the liquid production capacity of fractured and nonfractured ends of fractured tight oil reservoirs by changing the fracture length, soaking time, and depressurization method. 42 The results show that increasing the fracture length can improve the recovery rate and the recovery rate of the pore in the core near the fracture end is effectively improved. Bejestani et al studied the effects of porosity and permeability of the rock matrix on oil recovery when CO 2 is injected under different miscible conditions (primary miscible, near miscible, and immiscible).…”
Section: Introductionmentioning
confidence: 93%
“…The existence of fractures reduces the pore seepage resistance and increases the contact area between CO 2 and matrix pores, which is conducive to the extraction of the crude oil from smaller pores . Qian et al studied the liquid production capacity of fractured and nonfractured ends of fractured tight oil reservoirs by changing the fracture length, soaking time, and depressurization method . The results show that increasing the fracture length can improve the recovery rate and the recovery rate of the pore in the core near the fracture end is effectively improved.…”
Section: Introductionmentioning
confidence: 99%
“…Shen and Sheng carried out experiments and built a core-scale simulation model to investigate the asphaltene deposition in shale and reported that the CO 2 penetration depth and CO 2 concentration were the dominant factors in asphaltene precipitation. Moreover, the research on asphaltene precipitation on the tight cores during the soaking process mainly focused on permeability reduction. The microscopic asphaltene precipitation distribution in the pores and its comparison with CO 2 flooding have been rarely studied.…”
Section: Introductionmentioning
confidence: 99%